Wobblies on the Wallaby. (1st November 2015) - Day, Rowan; Cottle, Drew
Abstract : This article draws attention to the dominant but neglected rural dimension of the Industrial Workers of the World (IWW) in Australia. We argue that wandering bush workers formed the bulk of the IWW in Australia, whereas most studies have emphasised the role of the IWW's Sydney "Local." In overturning the dominant interpretation of the composition and character of the IWW in Australia, this article also shines light on an under-examined demographic feature of early twentieth-century Australia. By clarifying that the majority of Wobblies worked in the bush, we also show how the swagman, the itinerant worker of rural life, so prominent in our understanding – and our imaginations – of late nineteenth-century Australia, remained a prominent feature of the New South Wales and Queensland rural workforces during the early decades of the twentieth century. To put it simply, Australia had not settled down and neither had its most revolutionary unionists.